“This is all for high heid yins , what about Scottish women?”: Clashing expertise, fraught collaborations, and the 1983 Scottish Women's Health Fair - Karissa R. Patton (History of the Human Sciences, 2026)
In May 1983, two women's health events were held in Scotland. The first was the Women and Health Conference (WAHC), co-organised by the Scottish Health Education Group (SHEG) and the World Health Organization (WHO) European Region. This conference was held in the town of Peebles, Scotland and hosted approximately 200 invited delegates, largely from Europe and North America. The second event, the Scottish Women's Health Fair (SWHF) was designed in direct response to the “closed and elite” WAHC and welcomed over 2,000 women from across Scotland to Edinburgh's city centre at the end of May. Using the archival materials from the SWHF and the WAHC and oral history interviews with SWHF organisers, this paper analyses the intersection and divergences between the grassroots approach of the SWHF and the national and global health agendas of the WAHC. I also explore the personal and collective ramifications of these fraught collaborations. While the SWHF ultimately remained “associated” and occurred alongside the conference, the organisers of the fair designed their event in opposition to the WAHC's top-down, medicalised, and universalised women's health agenda. In theory, these were two associated events and both had support from the SHEG. But in reality, the history of these two women's health events underscores deep professional and feminist divides about how to approach women's health issues and who was best positioned to effect change.